The Voluntary Adoption of Internationally Recognized Accounting Standards and Firm Internal Performance Evaluation - Wu, Joanna Shuang; Zhang, Ivy Xiying (The Accounting Review, 2009)
ABSTRACT: A large body of research is devoted to understanding the causes and consequences of firms' adoption of internationally recognized accounting standards. Thus far, researchers' attention has focused almost exclusively on the informational benefits of the adoption. We extend the existing literature by offering a different, stewardship perspective. We hypothesize that the voluntary adoption of international accounting standards is associated with changes in the firm's internal performance evaluation process; in particular, it is associated with increases in the sensitivities of CEO turnover and employee layoffs to accounting earnings. Our results are consistent with these predictions.